The Body as a Toolbox in Ancient Egypt - Kootz, Anja (AAeO - Afrikanistik-Aegyptologie-Online, 2021)
This article is the revised version of a presentation at the International Workshop “The Body as a Toolbox” (Cologne, October 2018). It can discuss only some aspects of body conceptions in Ancient Egypt and will focus on few anthropological issues. An overview of the Ancient Egyptian idea of man will be given, including corporal as well as intellectual and social aspects. These aspects are not only to be considered separately, but intertwined. First, the Ancient Egyptian idea of the origin of human beings and its basic condition (anthropogenesis) will be presented, because it represents the reflection on human nature (anthropology). This nature comprises different aspects (Corporeality/ Ka/ Ba/ Heart/ Name/ Shadow und Ach), which need a short introduction. Then the human body will be described with regard to its capabilities of perception and interaction. At this point we also talk about single body parts as symbol for special skills. Ancient Egyptien sources also combine body parts with material culture. Finally, the idea of human beings’ ambivalence or its complexity will be illustrated by a primary source (The Struggle between Horus and Seth).